A DESCRIPTIVE STUDY OF LEXICAL COHESION IN FROZEN II MOVIE - Luki Mahfut Efendi; Wageyono; Wiwin Indiarti (LUNAR, 2022)
Objectives of this research are to identify types and functions of lexical cohesion and the most dominant one in Frozen II movie. The researcher employs descriptive qualitative method by downloaded movie’s script from internet and classified the lexical cohesion in utterances of the main characters in script of Frozen II movie. After collecting and selecting the data, the researcher starts to analyze the data by using Miles and Huberman's qualitative data analysis method. The method consists of three steps, namely data reduction, data display, and verification and conclusion drawing. The results show that in Frozen II movie there were 151 utterances of lexical cohesion. They are 110 data of reiteration and 41 data of collocation. In reiteration was found 94 repetitions, 9 synonyms, 3 superordinates, and 4 general words. In collocation was found 17 antonyms and 24 unordered lexical sets. The lexical cohesion that often used by authors in Frozen II movie was reiterations in order to send implicative meaning which hoped understood by viewers. Furthermore, the researcher finds reiteration as the most dominant type.